2010
DOI: 10.1029/2010gl044219
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a flux transfer event generated by multiple X‐line reconnection at the magnetopause

Abstract: [1] Magnetic flux transfer events (FTEs) are signatures of unsteady magnetic reconnection, often observed at planetary magnetopauses. Their generation mechanism, a key ingredient determining how they regulate the transfer of solar wind energy into magnetospheres, is still largely unknown. We report THEMIS spacecraft observations on 2007-06-14 of an FTE generated by multiple X-line reconnection at the dayside magnetopause. The evidence consists of (1) two oppositely-directed ion jets converging toward the FTE t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
179
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 134 publications
(190 citation statements)
references
References 20 publications
9
179
2
Order By: Relevance
“…The peculiarity of this FTE is that the ions stream northward (positive L direction) and westward (positive M direction) at the leading part of the FTE, but reverse direction at the turning point of the B N component. Based on the theory of Lee and Fu [1985], these two oppositely directed flows converging toward the center of the FTE are produced by multiple X line reconnection occurring beside the FTE, which is confirmed by the active FTE cases reported by Hasegawa et al [2010] and Zhang et al [2008]. This distinctive flow in the FTE suggests that this FTE has been freshly formed.…”
Section: Phase Bsupporting
confidence: 53%
“…The peculiarity of this FTE is that the ions stream northward (positive L direction) and westward (positive M direction) at the leading part of the FTE, but reverse direction at the turning point of the B N component. Based on the theory of Lee and Fu [1985], these two oppositely directed flows converging toward the center of the FTE are produced by multiple X line reconnection occurring beside the FTE, which is confirmed by the active FTE cases reported by Hasegawa et al [2010] and Zhang et al [2008]. This distinctive flow in the FTE suggests that this FTE has been freshly formed.…”
Section: Phase Bsupporting
confidence: 53%
“…This signature has been used in many studies to identify diffusion region encounters, and also in developing statistics that are used to characterize the average location of reconnection sites in the magnetotail. However, multispacecraft studies in the magnetotail (e.g., Eastwood et al 2005) and at the magnetopause (e.g., Hasegawa et al 2010;) have shown that this signature alone can be misleading. Signatures that conventionally would be interpreted as a single X-line moving in one direction could in fact be an O-line (at the center of a flux rope bounded by two active X-lines) moving in the opposite direction.…”
Section: Contrasting Reconnection X-lines and O-lines (Flux Rope) Sigmentioning
confidence: 99%
“…Observations by the four-spacecraft Cluster mission ) have contributed to analysis of the motion of FTEs and the open magnetic field lines at the magnetopause (e.g. Owen et al, 2001Owen et al, , 2008Wild et al, 2001;Dunlop et al, 2005;Fear et al, 2005Fear et al, , 2008Fear et al, , 2009Fear et al, , 2010Fear et al, , 2012Hasegawa et al, 2006Hasegawa et al, , 2010Farrugia et al, 2011). The tetrahedral configuration of the four spacecraft and their variable separation have provided a platform for reconstruction methods to determine the cross-sectional profiles of FTEs using, for example, Grad-Shafranov techniques (e.g.…”
Section: A Varsani Et Al: Analysis Of High-time-resolution Observatmentioning
confidence: 99%